Childhood Esophagitis Changes in 30 Years at 1 Center. Issue 5 (November 2015) - Memon, Zebunnissa; Baker, Robert D.; Khan, Abdur; Baker, Susan S.
Abstract : ABSTRACT: Eosinophils are nonspecific harbingers of esophageal disease. We report on the incidence and features of esophageal eosinophilia diagnosed at our center in 2011 and compare the findings with previously published results between 1980–1988 and 2000–2002. Eosinophils per high-power field were counted in esophageal biopsies from 675 patients who underwent 710 endoscopic procedures between January 1, 2011, and December 31, 2011. Of these, 209 (33%) patients were infiltrated with eosinophils; the other 466 (67%) showed no pathological changes. The highest concentrations of eosinophils were observed in the distal esophagus. Our findings also indicate that esophageal eosinophilia fluctuates over time.